Patient‐reported outcomes after minimally invasive retroperitoneal pancreatic necrosectomy to treat acute pancreatitis: An exploratory study. Issue 10 (21st September 2021) - Zelga, Piotr; Rees, Jonathan; Iaculli, Edoardo; Johnson, Colin; Jah, Asif
Abstract: Objective: The aim of this study (abbreviated as QUANTUM) was to assess the quality of life (QoL) of patients who underwent minimally invasive retroperitoneal pancreatic necrosectomy (MIRPN) for acute pancreatic necrosis with or without infection of necrotic tissue collections after discharge and to compare the patient‐reported outcomes (PRO) in these patients with published data in normative population. Methods: Patients with acute pancreatitis who underwent MIRPN between January 2010 and December 2016 were identified and invited to complete the European Organisation for Research and Treatment of Cancer (EORTC) QLQ‐C30 and EORTC PAN28(CP) questionnaires. PRO were compared using Pearson correlation coefficient and ANOVA (significance P < 0.01) with an age‐ and sex‐matched normative population of western Europe, stratified by age, and also the time duration after MIRPN (<3 y and >3 y). A change >15 points in the PRO score was taken as clinically important. Results: Among 52 eligible patients identified, 46 (88%) agreed to participate, 74% returned questionnaires. After the MIRPN all patients had worse physical and social functioning scores with a clinically important (>15 points) reduction in those ≤50 years; while fatigue, pain and insomnia symptom scales had the highest scores (42, 26 and 30 points, respectively). Patients <3 years after MIRPN had similar scores for all functional scales and global health‐related quality of life (HRQoL) compared to the normative population. However, over time their global HRQoL deteriorated and after 3 years their scores for functioning and symptoms were statistically ( P < 0.0001) and clinically (>15 points) worse than those in age‐matched controls. Conclusions: During the first 3 years after the MIRPN patients have a relatively high QoL but report worse fatigue than the normative population. However, patients should be informed that their HRQoL deteriorates with time, often due to chronic pancreatitis and pancreatic insufficiency. This study supports the use of MIRPN and prospective studies of HRQoL in this setting are indicated. Abstract : A minimally invasive retroperitoneal pancreatic necrosectomy (MIRPN) in the treatment of patients with severe acute pancreatitis resulted in a simlar health‐related quality of life (HRQoL) to that of the normative population. This benefit appears to persist in the first 3 years after the initial MIPRN, although they experience worse fatigue than the normative population. However, HRQoL deteriorates with time, often due to chronic pancreatitis and pancreatic insufficiency. Abbreviation: EORTC, European Organisation for Research and Treatment of Cancer.